Genetic Relationships Among Portuguese Cultivated and Wild Vitis vinifera L. Germplasm - Cunha, Jorge; Ibáñez, Javier; Teixeira-Santos, Margarida; Brazão, João; Fevereiro, Pedro; Martínez-Zapater, José M.; Eiras‐Dias, José E. (Frontiers in Plant Science, 2020)
The domesticated grapevine was been spread along the winemaking route from the primary Near East domestication point, were the greatest genetic diversity is found in wild vine populations. Portuguese wild populations are on the southwestern fringe of the distribution of the Vitis vinifera subsp. sylvestris in Europe. During the last Glacial Period they became isolated from the previous continuum that had been the territory of wild vine populations. Archaeological remains of domesticated sativa grapevines in Portugal date back from 795 BCE in the lower Tagus river basin. In this work, over 258 Portuguese sativa varieties and sylvestris plants were characterized using 261 SNP markers. The study of the genetic diversity of this local germplasm, its population structure and kinship, all framed in their historical and geographical backgrounds, has revealed a complex and structured network of first degree relationships, where only Iberian varieties are involved. Knowing the wild maternal lineage of the Iberian Peninsula (chlorotype A), it is though that an important number of Portuguese grapevine varieties derive, directly or indirectly, from originally local wild populations, supporting the occurrence of secondary events of local domestication. Some Iberian genotypes, like Alfrocheiro (Bruñal, in Spain), Sarigo (Cayetana Blanca), Mourisco Branco (Hebén), Amaral (Caiño Bravo) and Marufo (Moravia Dulce) are ancestors of a considerable number of all the autochthonous analyzed varieties. The uniqueness of these descendent varieties may be an outcome of complex natural hybridization or human-driven crosses. The diversity later developed was mostly local. Besides, evidence of introgression of domesticated germplasm into wild vines was found, substantiating the high risk of genetic erosion of the sylvestris subspecies.